Using sequential feeding of Optaflexx and Zilmax to improve performance and meat quality in cull beef cows - Daniel, M.J.; Dikeman, Michael E.; Houser, Terry A.; Unruh, John A.; Jaeger, John R.; Murray, Leigh W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Beef cows are culled from herds because of reproductive inefficiency, poor performance, old age, or farm downsizing due to high production costs. The National Market Cow and Bull Beef Quality Audit of 1999 reported that challenges associated with cull cow carcasses are undesirable dressing percentages and meat yields. Since 1999, an increasing number of producers are either selling cows in better physical condition or feeding cows a high concentrate ration for 50 to 100 days prior to harvest. According to the 2007 audit, cow carcasses were heavier and leaner and had more desirable muscle and fat color scores than in 1999. Although these improvements are positive steps toward increasing the value of cull cows, use of growth promoting agents, such as steroid implants and β-adrenergic agonists, can increase muscling and leanness more efficiently than feeding a concentrate ration alone. Currently, there are two β-agonists on the market for use in beef cattle in the United States: Optaflexx (ractopamine hydrochloride; Elanco, Greenfield, IN), a β1-agonist, and Zilmax (zilpaterol hydrochloride; Intervet Inc., Millsboro, DE), a β2-agonist. These growth promotants have been studied individually and in combination with implants (primarily in young steers and heifers), but no research published to date has investigated feeding a sequence of these growth promoting agents. Therefore, our objective was to investigate effects of feeding Optaflexx for 25 days followed by Zilmax for 20 days plus a 3-day withdrawal on cull cow performance, carcass traits, and meat quality.
Keywords: Beef; Cattle; Optaflexx; Zilmax; Performance; Meat quality